Role of Leadership in Structuring the Digital Transformation Journey in an Organisation - Dhawan, Ritu (Digital Repository of Theses - SSBM Geneva, 2024)
Industries are changing and adapting new technology at an amazing rate thanks to digital change. It includes a lot of different changes caused by technology, going back and forth between digitization, digitalization, and true digital transformation. There are gaps which need to be fully understood about how much things have changed because of technology, it's important to know the difference between these terms. It is not digitising, digitalizing, or digital transformation when you scan or print data or turn anything into soft data. Making data machine-readable, scanning documents, and changing paper records into digital ones are all steps that can be taken to start the digitalisation process. Businesses are investing millions of dollars on digital transformation projects, but a large number of them fail. The objective of this study is to learn more about digital transformation, challenges faced in the industry and understand why the failure rate of digital transformation is high, despite the rapid change and lots of investment in the digital transformation projects in many industries. This article consolidates the current state of the literature about business-level digital transformation to understand its roots and origins, assisting managers in the formulation and implementation of their firms' digital transformation initiatives. The goal is to summarise research on the leadership strategy, content, and context of digital business transformation, add fresh perspectives on how to position digital change and reveal the features that set it apart from earlier technology-enabled revolutions. The research was done through exploring journals, blogs, and conference papers. Then online survey and subsequently questionnaire round with likert scale analysis led to the results that Leaders play a crucial role in bringing success to digital transformation initiatives of the organisation. In addition to aligning technology investments with business goals, they should also take into account insider knowledge more than outside advice, allay insiders' fears of losing their jobs, fully comprehend how changes will affect the customer experience, and use tech-inspired process techniques (prototyping, experimentation, etc.) to facilitate change. The initial steps they have to take would be to understand old outdated systems, analyse and verify their needs and then plan with aligning goals and targets of their teams to turn them into different online apps. Next step would be to evaluate the ways how different apps would be integrated, cloud computing would be used, and the latest ERP to be implemented for various functions of the organisation. The digital transformation journey could start with CRM for Sales and Marketing, Account Payable and Account Receivable for Finance, Payroll and Employee management softwares for HR, Supply chain management software for Production and Logistics etc. Then with this advancement the organisations can start looking forward to AI and machine learning, blockchain, IoT, sensors, beacons etc. Therefore the research was able to identify the type of vision and planning Leaders need to formulate for the digital transformation journey, however, it still needs to be understood that the real Digital Transformation of a company is much more than these things. The role of leaders in transforming their organisation digitally is humongous, it can be achieved through the ways and means formulated in this study but there still remains a lot to be explored on what could be the right kind of vision and strategy based on the specific industry. The role of leaders in structuring digital transformation journeys specific to an industry needs to be understood and explored further.